Clinicopathological significance and potential drug target of RUNX3 in breast cancer - Yu YY; Chen C; Kong FF; Zhang W (Dove Medical Press, 2014)
Ying-Ying Yu,1 Chao Chen,2 Fan-fei Kong,2 Wei Zhang1 1Obstetrics and Gynecology Hospital, Fudan University, Shanghai, People’s Republic of China; 2Department of Gynecology, Shanghai First Maternity and Infant Hospital Affiliated to TongJi University, Shanghai, People’s Republic of ChinaBackground: Previous reports indicate that RUNX3 is a tumor suppressor in several types of human tumors, including breast cancer (BC). However, the correlation between RUNX3 hypermethylation and the incidence of BC remains unclear. In this study, we conducted a systematic review and meta-analysis aiming to comprehensively assess the potential role of RUNX3 hypermethylation in the pathogenesis of BC. Methods: A detailed literature search was made to identify studies for related research publications. Methodological quality of the studies was evaluated. Analysis of pooled data was performed. Odds ratio (OR) was calculated and summarized respectively. Results: Final analysis of 565 BC patients from eleven eligible studies was performed. The results showed that RUNX3 hypermethylation was significantly higher in BC than in normal breast tissue, the pooled OR from nine studies including 339 BC and 248 normal breast tissue (OR =24.12, 95% confidence interval [CI] =13.50–43.11, Z=10.75, P<0.00001). Further analysis also showed significantly increased OR of RUNX3 hypermethylation in estrogen receptor (ER)-positive than in ER-negative BC patients (OR =5.67, 95% CI =2.69–11.95, Z=4.57, P<0.00001). In addition, RUNX3 messenger RNA (mRNA) high expression was found to be correlated to better overall survival in 3,455 cases of BC patients that were followed up for 20 years (hazard ratio [HR] 0.79, P=8.8×10-5). Interestingly, RUNX3 mRNA overexpression was found to be correlated to better overall survival in only 668 cases of ER-negative patients (HR 0.72, P=0.01), but not in 1,767 cases of ER-positive patients (HR 0.87, P=0.13).Conclusion: The results of this meta-analysis suggest that RUNX3 hypermethylation may be implicated in the pathogenesis of BC. Detection of RUNX3 mRNA may be a helpful and valuable biomarker for diagnosis of BC, especially in ER-negative BC. We also discussed the significance of RUNX3 as a potential drug target. Keywords: methylation, tumor suppressor gene, meta-analysis, odds ratio